Report of the 15th International Scientific Conference on Transformation Processes in Sport “Sports Performance” - Miomir Maros (Journal of Anthropology of Sport and Physical Education)
The article discusses the highlights of the 15th International Scientific Conference on Transformation Processes in Sport “Sports Performance”, which was held in Budva, Montenegro. The event comprised oral and poster sessions. At the opening of the conference they spoke Rector of the University of Montenegro Danilo Nikolic, Sports Minister Nikola Janovic, Stevo Popovic, Dean of the Faculty for Sport and Physical Education at University of Montenegro. The prestigious conference “Transformational processes in sport - sports achievements” gathered 350 participants from 24 countries of the world, from four continents.